2021
DOI: 10.5811/westjem.2021.6.51306
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Use After Buprenorphine Prescription in a Community Emergency Department: A Cohort Study

Abstract: Introduction: Recent studies from urban academic centers have shown the promise of emergency physician-initiated buprenorphine for improving outcomes in opioid use disorder (OUD) patients. We investigated whether emergency physician-initiated buprenorphine in a rural, community setting decreases subsequent healthcare utilization for OUD patients. Methods: We performed a retrospective chart review of patients presenting to a community hospital emergency department (ED) who received a prescription for buprenor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Estimated program effects were also likely determined by unmeasured interventions to address OUD that were implemented in treatment or comparison group sites. For example, ED buprenorphine prescribing has been shown to be associated with increased postdischarge treatment engagement, 50 , 51 , 52 and MOUDs have been associated with lower risk of overdose. 8 , 53 , 54 In a study demonstrating that patients who received an ED-based intervention from a substance use navigator had greater treatment initiation, treatment initiation was increased further with ED-administered medication.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated program effects were also likely determined by unmeasured interventions to address OUD that were implemented in treatment or comparison group sites. For example, ED buprenorphine prescribing has been shown to be associated with increased postdischarge treatment engagement, 50 , 51 , 52 and MOUDs have been associated with lower risk of overdose. 8 , 53 , 54 In a study demonstrating that patients who received an ED-based intervention from a substance use navigator had greater treatment initiation, treatment initiation was increased further with ED-administered medication.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with opioid use disorder (OUD), EDs have expanded lifesaving buprenorphine prescribing and take-home naloxone programs nationwide, 20,21 activities that undoubtedly have improved the care for patients with OUD. [22][23][24] In contrast, there is currently a paucity of pharmacotherapy, psychosocial interventions, and harm reduction strategies targeting patients with methamphetamine use disorder. In this study our primary objective was to identify the motivations of people who use methamphetamine and their experiences in the ED.…”
Section: Introductionmentioning
confidence: 99%
“… 8 14 Further, a recent community-based study by Le et al demonstrated decreased subsequent healthcare utilization at 12 months after initiation of MOUD in the ED. 15 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Further, a recent community-based study by Le et al demonstrated decreased subsequent healthcare utilization at 12 months after initiation of MOUD in the ED. 15 Most ED-initiated MOUD studies have focused on treatment retention in large, urban, academic medical centers outside the Southeast or subsequent healthcare utilization in community hospitals. 7,11,12,15,16 Our large, urban, academic ED in the Southeast offers a unique perspective on the impact of ED-initiated MOUD on healthcare utilization in a resource-limited region characterized by persistent Medicaid non-expansion, high poverty rates, and healthcare access challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation